Pendampingan Pembelajaran Matematika bagi Siswa Kelas X B MAN 1 Probolinggo pada Materi Bentuk Akar - Ardilatus Sholehah; Dwi Riska Nur Wahyuni; Eka Titik Susiani; Fiisyatil Kamilah; Intan Putri Wardani; Shofia Hidayah (SANISKALA : Jurnal Pengabdian Masyarakat, 2026)
The Community Service Program (PKM) on Mathematics Tutoring for Grade X B Students of MAN 1 Probolinggo on the Topic of Radical Forms was conducted to enhance students’ understanding of the relationship between exponents and radicals. Preliminary observations revealed that most of the 19 male students in the class faced difficulties in mastering the basic concept of exponents, which affected their comprehension of radical expressions. The program was implemented over six weeks with one session per week using a tutoring-based learning approach. The implementation consisted of five stages: planning, pretest, tutoring sessions, posttest, and evaluation. The results showed an increase in the average score from 46 on the pretest to 80 on the posttest, along with improved motivation and active participation during learning activities. Therefore, this PKM activity proved effective in strengthening students’ conceptual understanding of radicals and can serve as an alternative strategy to address learning difficulties in mathematics at the senior high school level.